Genetıc dıvergence among bottle gourd genotypes - Rahaman, MM; Hossain, MK Hossain; Alam, Nazmul (Bangladesh Journal of Botany, 2025)
A field experiment was conducted at the farm of ACI Plant Genetics Research and Development Center (APGRDC), Mawna, Gazipur, during 2020 - 2021 to assess genetic diversity among 30 bottle gourd [Lagenaria siceraria (Molina) Standl.] genotypes across eleven agronomic traits. Multivariate analyses, including PCA, PCoA, CVA, and cluster analysis, were performed. Based on PCA scores and Mahalanobis' D² statistics, six distinct clusters were identified. Cluster I contained the most significant number of genotypes (15), while Cluster IV had only one. The significant inter-genotypic distance was recorded between BG10 and BG16, while BG8 and BG21 showed the least divergence. Maximum inter-cluster distance occurred between Clusters V and III, suggesting wide genetic variability, whereas the lowest was between Clusters V and VI. Cluster VI exhibited the highest intra-cluster variability. Trait-wise, Cluster VI was superior in yield per plant, average fruit weight, fruit length, and vine length; Cluster II excelled in flowering- and harvest-related traits; Cluster I had the longest internode and delayed female flowering; and Cluster III had the highest fruit number per plant. Genotypes BG14, BG19, BG20, Hajari, BG22, BG23, and BG25 were identified as promising parents for hybridization to exploit heterosis for yield improvement. Bangladesh J. Bot. 54(3): 455-463, 2025 (September)